Latinx Literature Unbound : Undoing Ethnic Expectation - Rodriguez, Ralph E. (Ralph Edward), 1965- (Book collections on Project MUSE., 2018)
Since the 1990s, there has been unparalleled growth in the literary output from an ever more diverse group of Latina/o writers. The extant criticism, however, has yet to catch up with the diversity of writers we label Latina/o and the range of themes about which they write. Little sustained scholarly attention has been paid, moreover, to the very category--Latina/o--under which we group this literature. Latina/o Literature Unbound, thus, begins with a fundamental question "What does it mean to label a work of literature or an entire corpus of literature Latina/o?" From this question a host of others spin out: What does that grouping allow us to see, predispose us to see, and preclude us from seeing? If the grouping--which brings together a heterogeneous collection of people and groups under a seemingly homogeneous label--tells us something meaningful, is there a poetics we can develop that would facilitate our analysis of this literature? In answering these questions, Latina/o Literature Unbound seeks to unbind Latina/o literature from taken-for-granted critical assumptions about identity and theme. It argues that there may be more salubrious taxonomies than Latina/o for organizing and analyzing this literature. Following a neo-formalist interpretive model that privileges reading as a temporal, meaning-making event, the book argues that genre may be a more durable category for analyzing this literature. Finally, Latina/o Literature Unbound suggests some ways in which we might want to proceed as we move forward with future studies of the writing we have come to identify as Latina/o.